Processing and high-temperature ductility studies of powder metallurgy Al-Li composites - Zhang, Xi (2009)
In recent years, aluminum-lithium (Al-Li) alloys along with aluminum based metal matrix composites (MMCs) have attracted a lot of attention as advanced materials due to their high specific strength and modulus. But their inherent brittle nature makes processing of these materials difficult using conventional metal forming techniques thereby limiting their applications. This problem could be overcome by making use of superplastic forming techniques. The aim of this research is therefore, to study the deformation behavior of powder metallurgy (P/M) silicon carbide particle reinforced Al-Li MMCs under isothermal and thermal cycling condition and to find out the potential of superplasticity in this composite system.